Fathers' emotional intelligence and their response towards their children's behaviors - Mirza, Mojgan; Redzuan, Ma'rof; Abdullah, Rohani; Mansor, Mariani (Canadian Center of Science and Education, 2010)
Emotional intelligence (EI) measures one’s “common sense” and ability to get along with others. The EI construct is a rather novel concept with little empirical support, particularly, in relation to the link between father’s EI and that of his child’s behavior. The specific objective of this research is to determine the relationship between fathers’ EI and their pleasure-anger responses to children’s behavior. The present study was carried out among 107 fathers of Iranian students in the Iranian primary school located in Kuala Lumpur, Malaysia. The students were clustered in three different age groups, 8, 9, and 10 years old. Data were collected using the Emotional Quotient Inventory (EQ-I) adult version (Bar- on EQ-I, 1997) and Parent Affect Test (PAT, Linehan and Egen, 1983). Pearson’s correlation indicated that fathers with high EI displayed more positive responses to children’s behavior in comparison to the fathers with low EI. In addition, fathers with low EI displayed more anger responses to children’s behavior in comparison to the fathers with high EI.